Öğretmenlik Eğitiminde Kazandırılan Yeterliklerin Öğretmenlik Mesleği ile Uyumu: Öğretmen Görüşlerine Dayalı Bir Karma Araştırma - ÇAKIR, GÖKÇEN SEYRA; ALPAYDIN, YUSUF (My University, 2019)
Eğitim fakültelerinin öğretmen adaylarına kazandırdığı bilgi ve becerilerin iş gerekleri ile ne ölçüde uyumlu olduğu sıklıkla tartışılmaktadır. Bu araştırmada öğretmen eğitimi programlarında sunulan iş gereği olarak öğretmenlik yeterlilikleri temel alınmakta ve söz konusu öğretmenlik yeterliliklere ilişkin alınan eğitime atfedilen önem ile mesleki uyum düzeyinin analizi amaçlanmaktadır. Karma bir desende planlanan araştırmada veriler, araştırmacılar tarafından geliştirilen Eğitim Fakültelerinin Öğretmen Yeterlikleri Kazandırma Durumları Ölçeği ve Öğretmen Yeterliklerinin Öğretmenlik Sürecindeki Önemi Ölçeği yardımıyla 2 ile 10 yıl arasında deneyime sahip 836 öğretmenden toplanmıştır. Ayrıca yarı yapılandırılmış görüşme formu yardımıyla 20 öğretmenden nitel veri toplanmıştır. Nicel veriler, ANOVA, korelasyon ve regresyon analizleri aracılığıyla, nitel veriler ise içerik analiz tekniği ile çözümlenmiştir. Araştırmanın bulgularında nicel ve nitel verilerin analiz sonuçlarına yer verilmiştir. Bunlar arasında, öğretmenlerin aldıkları eğitimin ve yeterlikleri atfettikleri önemin mezun oldukları üniversitelere göre farklılaşıp farklılaşmadığına, her iki ölçekteki altboyutların karşılıklı ilişkileriyle birlikte yordama düzeylerine ver verilmiştir. Tartışma bölümünde ise öğretmenlerin çalışma deneyimleri ile oluşan iş gereklerine ilişkin algıları ile aldıkları eğitimin uyumuna ilişkin değerlendirmeleri yorumlanmıştır. Farklı üniversitelerden mezun olan öğretmenlerin görüşleri alınarak elde edilen verilere göre farklı öğretmen eğitimi programları arasında karşılaştırmalar yapılmıştır.

To what extent knowledge and skills pre service teachers gain at the faculties of education are consistent with teaching experiences of inservice teachers has been extensively discussed. Thus, this study is mainly concerned with the teaching competencies developed in teacher education programs . In this light, it aims to explore whether the importance teachers place on teaching competencies attained during the preservice teacher training program complies with the job specifications of the teaching profession in practice. This study utilizes a mixed-methods research design. 836 teachers completed the Teaching Competency Attainment in Faculties of Education Scale and the Evaluation of the Importance Attributed to Teaching Competencies in In – Service Teaching Scale, both of which have been developed by the authors of this study. Teaching experience of the study sample ranged from 2 years to 10 years. In addition, a semi-structured interview form was prepared to collect the qualitative data. 20 teachers participated in the qualitative phase of the study. While ANOVA, correlation analysis and regression analysis were performed to analyze the quantitative data, a qualitative context analysis was used to analyze the qualitative data. The findings of the study include the results of the analyses of quantitative and qualitative data. Whether the importance teachers attributed to the teacher education program and the teaching competencies attained during the teacher education program differed according to the universities they graduated from was reported while indicating the relationships between the sub-dimensions of the aforementioned two scales. In the discussion section, the teachers’ views on the consistency between their teaching experience along with the job specifications of the teaching practice and their assessment of the teacher education program they went through were described in detail. Comparisons were made between different teacher education programs according to the data elicited from teachers who graduated from different universities.
The Consistency between the Teaching Competencies Attained during the Teacher Education Program and the Teaching Profession: A mixed methods research study based upon teacher perceptions